2005
DOI: 10.2105/ajph.2003.037093
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors for Fetal Alcohol Syndrome in the Western Cape Province of South Africa: A Population-Based Study

Abstract: Preventive interventions are needed to address maternal risk factors for FAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
188
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 57 publications
5
188
1
6
Order By: Relevance
“…In general, the factors associated with AEP risk in the present study are consistent with the maternal risk factors for FAS identified in previous studies in the Western and Northern Cape Provinces (May et al, 2005(May et al, , 2008Urban et al, 2008;Viljoen et al, 2002). However, parity was associated with lower risk of an AEP in this survey, but is usually associated with greater risk of having a child with an FASD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, the factors associated with AEP risk in the present study are consistent with the maternal risk factors for FAS identified in previous studies in the Western and Northern Cape Provinces (May et al, 2005(May et al, , 2008Urban et al, 2008;Viljoen et al, 2002). However, parity was associated with lower risk of an AEP in this survey, but is usually associated with greater risk of having a child with an FASD.…”
Section: Discussionsupporting
confidence: 92%
“…However, our assurances to the participants of the confidentiality of their responses and our exclusion of names on the questionnaires increase our confidence in the findings. Moreover, investigators of studies of similar South African communities have indicated their impressions that women are not inclined to under-report their alcohol use (e.g., May et al, 2005). Fifth, although findings regarding the Level 3 outcome would provide the greatest insight into the risk of actually having a child with FAS, our relatively small sample size precluded the execution of multivariate analyses for the urban site.…”
Section: Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Esto se explica, en parte, por el hecho de que los estudios de determinación activa de casos han sido realizados, en su mayoría, en poblaciones o grupos de alto riesgo (39). Entre los factores de riesgo maternos han sido señalados: estatus socioeconómico y nivel educativo bajos; nutrición pobre, menor altura y peso y menor masa corporal; edad avanzada y alto número de embarazos y partos (40,41).…”
Section: Prevalencia Del Saf Y Otros Teafunclassified
“…Although abruptio placentae is associated with many risk factors, such as cigarette smoking, growth restriction, hypertension and pre-eclampsia, 2,3 a local study showed that 60% of 70 multigravidas who had had intrauterine deaths due to placental abruption had unremarkable previous obstetric histories. 4 A high prevalence of cigarette smoking 5 and consumption of alcohol during pregnancy 6 have been noted in the coloured population, in which abruptio placentae is the main cause of stillbirth.…”
mentioning
confidence: 99%